Development of Quick-Solidifying Foamed Concrete for Mine Fires Extinguishment and the Basic Performances Tests - KeKuo, Yuan; Yu, Gong; Shaojun, Fu; Shuanhai, Xu; Kaide, Liu; Hongdan, Yu; Shan, Gao (Frontiers in Materials, 2020)
Coal mine fire has always been the main disasters in coal mining in various countries around the world, and several attempts have been made to develop many kinds of fire extinguishing materials and technology. Because of the salient features: high foaming factor(that means a small amount of raw materials can produce large-volume of foam concrete), widely source, eco-friendly and economical raw materials, cement-based inorganic foam concrete for engineering filling and coal mine fire extinguishing has become the first choice. But the shortcomings of traditional foamed concrete are obvious, short curing time, poor water retention capacity, foam burst easily, and can not be kept in the spontaneous combustion cavity area for a long time to accumulate and solidify; at the same time after the foam burst, the formation of cracks in the solidified body is sometimes not strict, and so on. So, traditional foamed concrete should be optimized and the aforementioned deficiencies could be overcome. The objective of this paper goes to propose quick-solidifying foamed concrete by laboratory test and to test these materials properties. The stability of the solidified body of the quick-solidifying foamed concrete, foamed concrete slurry fluidity, curability, shrinkage and cracking during solidifying, high temperature resistance and water resistance were tested and the laws and values of these characteristics were got. The results finally show the quick-solidifying foamed concrete developed in the paper with a good performance in implementation of high filling and fire prevention in big space of mine.